2019
DOI: 10.3390/ijerph16122182
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Conflict, School Connectedness and Depressive Symptoms in Chinese Adolescents: Moderation Effect of Gender and Grade Level

Abstract: This study examined the associations of interpersonal conflict and school connectedness with depressive symptoms in Chinese adolescents. A cross-sectional study was conducted among 6576 adolescents in Shenzhen, China. Participants completed a battery of questionnaires that assessed adolescents’ depressive symptoms, conflict with parents, teachers, and peers, school connectedness, and demographics. Multiple linear regression analysis was used to explore the association of interpersonal conflict and school conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 38 publications
0
19
0
1
Order By: Relevance
“…More broadly, these results appear to align with some recent international research in so far as depressive symptoms are associated with mental health-related disabilities. For example, research with adolescents living in China showed that relationships between school connectedness and depressive symptoms were stronger in adolescent girls than boys (He et al, 2019; see also the Chinese study by Zhao & Zhao, 2015). Earlier cross-sectional research in the United Kingdom (unrelated to the MCS dataset) also highlighted the link between school connectedness and depressive symptoms in adolescents (Millings, Buck, Montgomery, Spears, & Stallard, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…More broadly, these results appear to align with some recent international research in so far as depressive symptoms are associated with mental health-related disabilities. For example, research with adolescents living in China showed that relationships between school connectedness and depressive symptoms were stronger in adolescent girls than boys (He et al, 2019; see also the Chinese study by Zhao & Zhao, 2015). Earlier cross-sectional research in the United Kingdom (unrelated to the MCS dataset) also highlighted the link between school connectedness and depressive symptoms in adolescents (Millings, Buck, Montgomery, Spears, & Stallard, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…These questions were successfully used by a previous study conducted with Chinese adolescents [ 37 ]. Conflict with peers was assessed using 3 items: “In the past 12 months, have you ever had a serious quarrel with your fellow students at school?”, “In the past 12 months, have you been involved in physical fighting with your fellow students at school?” and “In the past 12 months, have any of your fellow students emotionally bullied you (humiliated, teased, or threatened you)?” These items have established predictive validity with Chinese students [ 37 ] and have successfully been used in our prior research into risk factors for mental health problems in Chinese adolescents [ 21 ]. This scale had an adequate internal consistency among Chinese adolescents in this study (Cronbach α = 0.73).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, conflict with teachers was measured with the following three items: “In the past 12 months, have you ever had a serious quarrel with your teachers at school?”, “In the past 12 months, have you been emotionally punished (such as being scold, threatened, or humiliated) by your teacher in the past 12 months?” and “Have you ever been physically punished (such as being forced to stand for some time, being beaten with fist or other objects, or being kicked) by your teacher in the past 12 months? These questions have been successfully used in previous research into risk factors for mental health problems in Chinese adolescents [ 21 , 37 ]. This scale also had a good internal consistency among Chinese adolescents in our study (Cronbach α = 0.75).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations